Baking quality of winter wheat - Gustafsson, Linnéa (2022)
Wheat is the most important cereal crop for breadmaking. Different wheat varieties tend to yield varying bread quality, which is affected both by genotype and environmental factors. The present study aims to investigate the genetic and environmental effect on bread quality. This was done to determine whether different breadmaking properties are most influenced by wheat variety, cultivation site or nitrogen supply. Seven winter wheat varieties were cultivated at two sites in Sweden, with varying amount of nitrogen fertilisation (one low and one high), resulting in four different environments. These samples were analysed to evaluate flour, dough and bread quality properties. The parameters were evaluated using principal component analysis (PCA) and those contributing most to the overall variance in data were further analysed using two-way analysis of variance (ANOVA). In the PCA, genetic and environmental differences formed an orthogonal pattern, influencing the bread quality parameters differently. Breadmaking properties, such as peak viscosity of the flour, bread volume and dough tenacity were linked to genotype, whereas protein content of the flour was linked to environment. For those samples that were cultivated with low nitrogen supply, cultivation site had no effect on the baking quality. For the samples cultivated in Svalöv, nitrogen supply did not have any effect on the baking properties. In conclusion, the genetic effect seems to be greater than the environmental effect on the breadmaking properties and bread quality. However, future research is needed to elucidate whether the observed patterns and obtained results can be confirmed and further explained in universal studies.